Consumer Protection Against Processed Food Advertisements with Misleading Health Claims - Moch Andry Wikra Wardhana Mamonto; Shendy Maria Fricella (PT Mattawang Mediatama Solution, 2023)
This research will answer the role of the Food and Drug Supervisory Agency (BPOM) towards Indonesian citizens as consumers in supervising processed food advertisements with misleading health claims, as well as the responsibility of business actors to consumers in Indonesia as the party that is harmed by business actors' promotional activities in the form of advertisements. which is misleading. This research was conducted using normative methods. The results of the study show that business actors must be responsible for misleading advertisements produced by business actors, as well as for processed food advertisements with health claims, a regulation is required that requires advertising materials to be registered through the Ad Registration System (SIREKA) page which is managed and approved by BPOM as product category of drugs and health supplements. Processed food advertising rules for carrying out the registration can provide certainty to consumers to find out the truth of claims about food product advertisements in circulation.